The WTO Promotes Trade, Strongly But Unevenly - Wei, Shang-Jin (IMF Working Papers; Working Paper, 2003)
This paper furnishes robust evidence that the GATT/WTO has had a powerful and positive impact on trade. The impact has, however, been uneven. GATT/WTO membership for industrial countries has been associated with a large increase in imports estimated at about 40 percent of world trade. The same has not been true for developing country members, although those that joined after the Uruguay Round have benefited from increased imports. Similarly, there have been asymmetric effects among sectors, with WTO membership associated with substantially greater imports in sectors where barriers are low. These results are consistent with the history and design of the institution, which presided over significant trade liberalization by the industrial countries except in sectors such as food and clothing; largely exempted developing countries from the obligations to liberalize under the principle of special and differential treatment; but attempted to redress the latter by imposing greater obligations on developing country members that joined after the Uruguay Round.